Principal Supervision at The Educational Unit Level: Implementation of Organizational Management and Control - Afriani, Linda; Bafadal, Ibrahim; Ubaidillah, Aan Fardani; Utari, Tria Ina; Chidayatiningsih, Rina (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This study aims to analyze the implementation of principal supervision at the educational unit level through a management and organizational theory approach. The method used is a systematic literature review with data sources in the form of national education regulations, classical to contemporary organizational theories (Weber, Taylor, Likert, Simons), and empirical research results in the period 2013–2023. Article selection was carried out based on the PRISMA (Preferred Reporting Items for Systematic reviews and Metaanalyses) guidelines, searches were conducted through Scopus, Web of Science, and Sinta (Indonesia), so that 20 articles were selected that met the inclusion criteria. The results of the study show that the implementation of principal supervision in Indonesia still faces various challenges, such as limited supervisor competence, minimal training, lack of technology utilization, and gaps between national policies and local practices. Analysis based on management theory reveals that the supervision system has not fully implemented the principles of bureaucracy, managerial efficiency, participatory leadership, and strategic control. Therefore, educational supervision reform is needed through mentoring-based supervision, digitalization of the supervision process, strengthening the capacity of supervisors and principals, and adjusting policies to local conditions. These findings are expected to provide theoretical and practical contributions in strengthening the effectiveness of the principal supervision system in Indonesia.